Serious hazards of transfusion (SHOT) initiative: analysis of the first two annual reports. Issue 7201 (3rd July 1999) - Williamson, L M; Lowe, S; Love, E M; Cohen, H; Soldan, K; McClelland, D B L; Skacel, P; Barbara, J A J
Abstract: Objective: To receive and collate reports of death or major complications of transfusion of blood or components. Design: Haematologists were invited confidentially to report deaths and major complications after blood transfusion during October 1996 to September 1998. Setting: Hospitals in United Kingdom and Ireland. Subjects: Patients who died or experienced serious complications, as defined below, associated with transfusion of red cells, platelets, fresh frozen plasma, or cryoprecipitate. Main outcome measures: Death, "wrong" blood transfused to patient, acute and delayed transfusion reactions, transfusion related acute lung injury, transfusion associated graft versus host disease, post-transfusion purpura, and infection transmitted by transfusion. Circumstances relating to these cases and relative frequency of complications. Results: Over 24 months, 366 cases were reported, of which 191 (52%) were "wrong blood to patient" episodes. Analysis of these revealed multiple errors of identification, often beginning when blood was collected from the blood bank. There were 22 deaths from all causes, including three from ABO incompatibility. There were 12 infections: four bacterial (one fatal), seven viral, and one fatal case of malaria. During the second 12 months, 164/424 hospitals (39%) submitted a "nil to report" return. Conclusions: Transfusion is now extremely safe, but vigilance is needed to ensure correct identification of blood and patient. Staff education should include awareness of ABO incompatibility and bacterial contamination as causes of life threatening reactions to blood.